ECOSYSTEMS OF INNOVATION AND THE ADOPTION OF THE INDUSTRY 4.0 MODEL IN SMES - A BIBLIOMETRIC STUDY (Journal of Industrial and Mechanical Engineering, 2021)
The following is a work based on a bibliometric research around the Industry 4.0 model, that looks for initiatives of the Industry 4.0 model, the barriers to its adoption, including the relative weight of cultural contexts, the geo-positioning of Latin America in the face of industry 4.0 model from other regions such as the USA, Germany, among others.In particular, the innovative ecosystem and border conditions in which companies find themselves will be analyzed, considering different and asymmetries between regions and sectors of the economy during the transition towards this model.Therefore, it will try to find barriers and challenges for the adoption of the Industry 4.0 model, and analyze how the innovation ecosystem can facilitate the adoption of the new model and what conditions need to be met.
Keywords: Industry 4.0; Innovation Ecosystems; SMEs; productivity